2008
DOI: 10.1038/npp.2008.176
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin1 Antagonists Potentiate Antidepressant Properties of Serotonin Reuptake Inhibitors, Yet Blunt Their Anxiogenic Actions: A Neurochemical, Electrophysiological, and Behavioral Characterization

Abstract: Though neurokinin 1 (NK 1 ) receptor antagonists are active in experimental models of depression, clinical efficacy has proven disappointing. This encourages interest in association of NK 1 receptor blockade with inhibition of serotonin (5-HT) reuptake. The selective NK 1 antagonist, GR205171, dose-dependently enhanced citalopram-induced elevations of extracellular levels of 5-HT in frontal cortex, an action expressed stereospecifically vs its less active distomer, GR226206. Further, increases in 5-HT levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Surprisingly, then, there was no phenotypic variation as regards the influence of MDMA upon 5-HT levels in dialysates of frontal cortex. Such a regional difference in the impact of MDMA on serotonergic transmission resembles observations with neurokinin1 receptor antagonists (Guiard et al, 2007;Gobert et al, 2009). …”
Section: Amplification Of the Influence Of Mdma Upon Locomotor Activitymentioning
confidence: 66%
“…Surprisingly, then, there was no phenotypic variation as regards the influence of MDMA upon 5-HT levels in dialysates of frontal cortex. Such a regional difference in the impact of MDMA on serotonergic transmission resembles observations with neurokinin1 receptor antagonists (Guiard et al, 2007;Gobert et al, 2009). …”
Section: Amplification Of the Influence Of Mdma Upon Locomotor Activitymentioning
confidence: 66%
“…Suzuki et al (2003) showed an attenuation of electrophysiological responses to noxious heat in the dorsal horn neurons in NK 1 receptor-knockout mice, whereas Budai et al (2007) reported diminished activity of on-cells in rostral ventral medulla following application of an NK 1 receptor antagonist (L-733,060). The source of potentation in the supraspinal limbic circuitry observed here could arise from the coupling between antagonist action on NK 1 receptors and the 5-HT system (Gobert et al, 2009;Valentino et al, 2003). One main finding by Valentino et al was a characterization of the 5-HT-driven inhibition of neuronal activity following substance P administration: an effect suppressed by treatment with an NK 1 antagonist (Sendide).…”
Section: Modulation Of Early-and Late-phase Cns Responses To Evoked Pmentioning
confidence: 80%
“…This concept is of particular interest because blockade of NK 1 receptors promotes the activity of corticolimbic adrenergic and dopaminergic pathways, complementing the effects of 5-HT reuptake inhibition. [173][174][175][176][177] Blockade of NK 1 receptors also accelerates the long-term facilitatory influence of SSRIs on serotonergic transmission, possibly by accelerating desensitization of inhibitory 5-HT 1A autoreceptors. [175][176][177] These observations suggest that dual agents may be both more effective and rapid-acting than SSRIs and, inasmuch as NK 1 antagonists enhance antidepressant actions of SSRIs yet curtail their anxiogenic effects, 3,177,178 they should be devoid of the symptoms of nervousness that patients may experience at the beginning of SSRI therapy.…”
Section: Neuropeptidergic Receptors As Targets: Focus On Neurokinin 1mentioning
confidence: 99%
“…248 Specific examples of drug combinations include a paroxetine (SSRI) plus vestipitant (NK 1 antagonist) formulation, and fluoxetine (SSRI) plus olanzapine (atypical antipsychotic). 20,177 Network concepts of CNS function and dysfunction: the need for early intervention Mood, cognition, and other functions disrupted in depression are emergent properties of overarching cerebral circuits, rather than of individual proteins, receptors, or neurons. The brain-its organization, operation, perturbation and treatment-is best understood in terms of functional modules and networks at a hierarchy of scales: from receptors, G-proteins, and their postsynaptic partners to neuronal circuits to regions such as the frontal cortex.…”
Section: Comparison Of Multitarget Agents To Drug Associationsmentioning
confidence: 99%